2010
DOI: 10.1007/s10661-010-1360-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of microbiological indicators of fecal pollution in the riverine substrates

Abstract: Distribution of fecal microorganisms in water, periphyton, and sediment was studied along the Žrnovnica river (Croatia) over a 1.5-year period. It was found that periphyton was inhabited by the highest number of investigated bacteria, while lower numbers of them were found in sediment and the lowest in surface water of the river. The concentrations of fecal microorganisms in periphyton and partly in sediment were found to be significantly higher in the middle of the river course, near the town of Žrnovnica, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This could be the consequence of variable interactions between E. coli cells and suspended matter (Rehmann and Soupir, 2009). However, Kovacic et al (2011) previously reported sediments to concentrate FI. The Chaudanne river geomorphological successions and water regime might explain these differences.…”
Section: Discussionmentioning
confidence: 98%
“…This could be the consequence of variable interactions between E. coli cells and suspended matter (Rehmann and Soupir, 2009). However, Kovacic et al (2011) previously reported sediments to concentrate FI. The Chaudanne river geomorphological successions and water regime might explain these differences.…”
Section: Discussionmentioning
confidence: 98%
“…The microbiological quality of water is classically monitored by searching for and quantifying bacterial indicators of fecal contamination. Total coliform, fecal coliform, fecal streptococci and enterococci are among the most frequently used microbial indicators of fecal pollution (Malik and Ahmad 2002;Cabral and Marques 2006;Djuikom et al 2006;Kovačić et al 2011). Although not usually harmful themselves, their presence may indicate the possibility of pathogen presence (Bonadonna et al 2002;Dorsey et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A tropism of bacteria for coarser particles such as quartz grains has also been reported (Ams, Fein, Dong, & Maurice, 2004). High concentrations of FIB (up to 5 × 10 5 most probable number [MPN] g −1 of dry weight) were reported in the literature for several water bodies, including beach sand and sediments from estuaries and other coastal areas (Craig, Cromar, & Fallowfield, 2002, Halliday & Gast, 2011); lakes (Ishii, Ksoll, Hicks, & Sadowsky, 2006), rivers (Craig et al, 2002; Donovan et al, 2008; Kovacic, Tripkovic, Galov, & Žitko, 2011), and infiltration aquifer recharge systems (Voisin, Cournoyer, Vienney, & Mermillod‐Blondin, 2018). Analyses of the relations between the finest fractions of sediments and the occurrence of bacteria suggested a strong impact of organic matter on their metabolic states (e.g., Characklis et al, 2005; Fischer et al, 2002; Voisin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%